2010
DOI: 10.1097/opx.0b013e3181f6fbb3
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Current Antibiotics for the Treatment of Bacterial Conjunctivitis

Abstract: Bacterial conjunctivitis is a common ocular infection that is generally treated empirically with a broad-spectrum antibiotic. The more common pathogens causing bacterial conjunctivitis include Staphylococcus aureus, Haemophilus influenzae, Streptococcus pneumoniae, Staphylococcus epidermidis, and Moraxella species. Several antibiotics traditionally used to treat bacterial conjunctivitis are no longer widely prescribed because of increased bacterial resistance and/or safety concerns. The introduction of the flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 97 publications
1
42
0
1
Order By: Relevance
“…These include shorter disease duration; prevention of spread of infection; reduction in adverse events (AEs), including those threatening vision; and reduced disease recurrence. 14,15 The socioeconomic impact of these benefits are significant, with decreased absenteeism from school and work. Moreover, the presence of red eyes may constitute a social and psychological burden 16 driving demand for medical treatment.…”
Section: Treatment Of Bacterial Conjunctivitismentioning
confidence: 98%
See 3 more Smart Citations
“…These include shorter disease duration; prevention of spread of infection; reduction in adverse events (AEs), including those threatening vision; and reduced disease recurrence. 14,15 The socioeconomic impact of these benefits are significant, with decreased absenteeism from school and work. Moreover, the presence of red eyes may constitute a social and psychological burden 16 driving demand for medical treatment.…”
Section: Treatment Of Bacterial Conjunctivitismentioning
confidence: 98%
“…This balanced, dual action may also partially account for the lower rate of resistance development to besifloxacin compared with older fluoroquinolones that preferentially target either one of these enzymes, because dual mutations are required for development of high-level resistance to besifloxacin. 15 A mutant-selection study showed that the proportion of isolates acquiring resistance to besifloxacin was nearly 2 orders of magnitude lower than those developing resistance to ciprofloxacin 23 ; further, because besifloxacin is not used for systemic indications, there is no possibility of developing resistance subsequent to systemic use. However, cross-resistance from bacteria developing resistance to other fluoroquinolones is still possible.…”
Section: Increasing Drug Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Topical antibiotics alone are effective in most cases of bacterial conjunctivitis, except in cases of gonococcal and chlamydial infection, which require systemic treatment [54]. Fluoroquinolones or aminoglycoside drops are an excellent initial choice of therapy for bacterial conjunctivitis.…”
Section: Bacterial Conjunctivitismentioning
confidence: 99%